Analysis of Spirit and Job Satisfaction on the Performance of Employees of PT. Dodorindo Jaya Abadi Tanjung Morawa - Etin Indrayani; Robin Robin (Jurnal Mantik, 2022)
This study aims to determine whether there is an influence of spirit and work satisfaction on the work performance of employees. The population in this study were all employees who worked at PT. Dodorindo Jaya Abadi Tanjung Morawa as many as 447 employees. The sampling technique used was the Slovin technique with a significance of 10% with a sample of 82 employees. In this study, a questionnaire will be distributed which is measured by a Likert scale. Data analysis used multiple linear regression analysis. The results showed that there was an effect both partially and simultaneously where the spirit variable partially had a tcount (4.694) greater than ttable (1.990) with a significant (0.00) less than 0.05, while the work satisfaction variable had a tcount value (5.950) is higher than ttable (1.990) with a significant (0.00) smaller than 0.05. Simultaneously, the variables of spirit and work satisfaction have a value of Ftable (3.11) and a significance = 5% (0.05), namely Fcount (25.338) and sig.a (0.000a). This shows that the results of the study accept Ha and reject H0, while the coefficient of determination R Square is 0.391. This shows that the variables of spirit and work satisfaction explain their influence on the work performance by 39,1%. While the remaining 60,9% is the influence of other independent variables not examined in this study.